Influence of Investment Literacy and Financial Risk Management on Investor Interest in Sharia Stocks: A Case Study in Bengkulu Province - Syaufuri, Intan Lhotifah; Wahyuni, Eka Sri; Indra, Yetti Afrida (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the influence of investment literacy and financial risk management on investor interest in sharia stocks, particularly in Bengkulu Province. With the increasing popularity of sharia investments, understanding these factors is vital for making informed investment decisions. Methodology: A quantitative approach was used, employing a structured questionnaire distributed to 89 investors in Bengkulu Province. The data were analyzed using multiple linear regression and classical assumption testing. Results: The findings reveal that both investment literacy and financial risk management significantly influence investor interest (p < 0.05). The adjusted R-squared value of 0.921 suggests that these factors explain 92.1% of the variation in investor interest. Findings: The study highlights the significant role of financial literacy and risk management in shaping investor interest in sharia stocks, indicating that more informed and risk-aware investors are more likely to participate in sharia investments. Novelty: This research provides new empirical evidence on the determinants of investor interest in sharia stocks, particularly in the context of Bengkulu Province, where limited research exists. Originality: The study is original in its focus on the regional market of sharia stocks and its contribution to the literature on investment behavior in Islamic finance. Conclusions: The study emphasizes the need for enhanced financial education to encourage more investor participation in sharia stock investments. Type of Paper: Research paper.